Experimental and numerical investigation on solid propellant rocket motor performance - Almayas, Ali A A A (2021)
Application of Computational Fluid Dynamics (CFD) in studying solid propellant rocket motor have been growing steadily. This is due to the fact that experimental work will cost more time and money. Other than that, the industry needs more understanding to guide designer for more reliable technical solution and less expensive in order to design solid rocket motor for missiles and space launchers. To bring new knowledge for solid rocket propulsion, CFD has been important and dependable. However, to validate the dedicated models and numerical simulation, experimental procedure was important. For the design process, solid propellant rocket with medium thrust produced been focused in the current work. The works are including experimental and CFD simulation approaches. For the experimental work, the static firing test will be used. As for the fabrication of the propellant grain, it been conducted at the authorized centre by the Malaysian authority. Meanwhile for the CFD simulation, the work will be focus on the internal flow inside the nozzle. The findings show that data has significant errors due to the failure of the SRM bulkhead during experimental analysis. Due to the Covid 19 pandemic, the experimental work cannot be repeated and therefore was presented as it was. Next findings show the normal nozzle with different throat length simulation. It was found that the throat length has significant impact on the performance of the nozzle flow. Finally, findings from parametric study about the dual bell nozzle. The results show that the dual bell nozzle can increase the effectiveness of the nozzle flow. In overall, the work has covered all the intended objectives and CFD analysis has been prove as useful design tools used to lessen the amount of physical testing that must be done to validate a design and measure its performance.